Is The Co-administration of Metformin and Clomiphene Superior to Induce Ovulation in Infertile Patients with Poly Cystic Ovary Syndrome and Confirmed Insulin-resistance: A Double Blind Randomized Clinical Trial - Azam Azargoon; Human Mousavi Fatemi; Majid Mirmohammadkhani; Satinik Darzi (Tehran University of Medical Sciences, 2023)
Objective: This study aimed to compare the effects of clomiphene citrate (CC) combined with metformin or placebo on infertile patients with poly cystic ovary syndrome (PCOS) and insulin resistance (IR). Materials and methods: We included 151 infertile women with PCOS and IR in a university hospital from November 2015 to April 2022 in this prospective, double-blind, randomized, placebo-controlled trial. Patients were randomized into two groups; group A: received CC plus metformin (n = 76) and group B: received CC plus placebo (n = 75). The ovulation rate was the main outcome measure. Clinical pregnancy, ongoing pregnancy, live birth and abortion rates were secondary outcome measures. Results: There was no remarkable difference in ovulation rate in two groups. Moreover, no significant changes were observed in clinical pregnancy, ongoing pregnancy, live birth and abortion rates between two groups. A larger proportion of women in group A suffered from side effects of metformin (9.3% versus 1.4%; p=0.064), although this was not significant. Conclusion: In IR infertile women with PCOS, metformin pre-treatment did not increase the ovulation, clinical pregnancy and live birth rates in patients on clomiphene citrate.